Soil and root nutrient chemistry structure root‐associated fungal assemblages in temperate forests. (1st June 2020) - Nguyen, Dung Quang; Schneider, Dominik; Brinkmann, Nicole; Song, Bin; Janz, Dennis; Schöning, Ingo; Daniel, Rolf; Pena, Rodica; Polle, Andrea
Summary: Root‐associated fungi (RAF) link nutrient fluxes between soil and roots and thus play important roles in ecosystem functioning. To enhance our understanding of the factors that control RAF, we fitted statistical models to explain variation in RAF community structure using data from 150 temperate forest sites covering a broad range of environmental conditions and chemical root traits. We found that variation in RAF communities was related to both root traits (e.g., cations, carbohydrates, NO3 − ) and soil properties (pH, cations, moisture, C/N). The identified drivers were the combined result of distinct response patterns of fungal taxa (determined at the rank of orders) to biotic and abiotic factors. Our results support that RAF community variation is related to evolutionary adaptedness of fungal lineages and consequently, drivers of RAF communities are context‐dependent.